sqrt (3)b + sqrt (2) = sqrt (7)b - 10
If I take it the way you typed it, then
√3b - √7b = -10 - √2
b(√3-√7) = -10-√2
b = (-10-√2)/(√3-√7) = appr. 12.5
or definitely not one of the answers given
Solve: sqrt (3)b + sqrt (2) = sqrt (7)b - 10
a) none
b) (3)
c) (-3)
d) (-4)
i need to know if my answer is correct or not and the answer i picked is a thanks
4 answers
I have tried several interpretations of the question as typed and in each case get none of the answers. Is what is typed a true presentation of the question?
Then the answer would be A...
No not A as there is a solution to each of the presentations of the question. It is just that the answers are not any of the remaining three.